Poziom wiedzy informatycznej uczniow klas młodszych - Gruba, Piotr (Wydawnictwo Naukowe UAM w Poznaniu, 1999)
The article describes the results o f the pedagogic research o f a level o f the information science knowledge o f the pupils from the primary classes o f elementary schools in Gliwice. After taking into account the two different types of schools: governmental and private the author discusses the similarities and différencies between the information science competencies o f the pupils. The general remarks concerned the program of additional lessons of information technology, hardware and needed competencies of the teachers are added.
A level o f the information science knowledge of the primary class pupils
Keywords: wiedza; knowledge; ocena; assessment; poziom umiejętności; skills level; kompetencje; competences; TIK; ICT